Say no to knowledge hiding: can ethical leadership help prevent it? - Mujib, Miftachul; Ulfa, Adilla Kustya (Universitas Dian Nuswantoro Semarang, 2024)
This study was conducted due to the scarcity of literature examining the impact of knowledge sharing climate on knowledge hiding. In line with that, many previous studies have focused on positive ethical leadership as an antecedent of knowledge hiding. However, no one has tested the moderating role of ethical leadership in helping to prevent knowledge-hiding intentions. This study aims to examine the influence of knowledge-sharing climate in organizations on knowledge-hiding behavior in the higher education sector and to test the moderating effect of ethical leadership in strengthening the influence of knowledge-sharing culture on knowledge-hiding behavior in the higher education sector. Data were collected from 156 lecturers from various state and private universities in Indonesia through a survey method. Data analysis was conducted using the SEM-PLS technique. The results showed a negative influence of knowledge sharing climate on knowledge hiding. Ethical leadership was proven to moderate the relationship based on the perceptions of several sample groups, except for the sample group with the generation category. This study contributes theoretically to complement the still limited literature that reviews the impact of a knowledge-sharing climate in preventing the emergence of knowledge-hiding behavior. Practically, the results suggest the need to implement ethical leadership to minimize the knowledge-hiding behavior of lecturers in higher education.